ANALISIS GAYA MUSIKAL PADA GENDING LAGU "JALI-JALI" KARYA KOKO KOSWARA - Yantiningtyas, Vita Rindri; Sentosa, Gempur (Paraguna, 2023)
"Jali-Jali" is a musical composition in the form of sekar gending (song with musical accompaniment) composed by Koko Koswara in 1970 using gamelan salendro. The main musical pattern used the Sundanese musical pattern and the gambang Kromong musical pattern. The unique musical characteristics of the combination of two different musical backgrounds are the main attraction for researchers to study 2 (two) aspects, namely musical form and style. The theory used in this research is the science of musical form by Karl-Edmund Prier SJ and the style theory from Bruno Nettl. The science of musical form is used to analyze melodic aspects (motives, sequences, phrases, and periods), and Bruno Nettl's theory of style is used to analyze Koko Koswara's musical style. The results of this research illustrate that Koko adapted several characteristics of the original "Jali-Jali" song from Betawi was combined with Sundanese music into the "Jali-Jali" song as a result of his arrangement so that the unique composition that Koko created was very different from Koko's musical works another.